An Approach for Economic Analysis of Intermodal Transportation - Sahin, Bahri; Yilmaz, Huseyin; Ust, Yasin; Guneri, Ali Fuat; Gulsun, Bahadir; Turan, Eda (HINDAWI LTD, 2014)
A different intermodal transportation model based on cost analysis considering technical, economical, and operational parameters is presented. The model consists of such intermodal modes as sea-road, sea-railway, road-railway, and multimode of sea-road-railway. A case study of cargo transportation has been carried out by using the suggested model. Then, the single road transportation mode has been compared to intermodal modes in terms of transportation costs. This comparison takes into account the external costs of intermodal transportation. The research reveals that, in the short distance transportation, single transportation modes always tend to be advantageous. As the transportation distance gets longer, intermodal transportation advantages begin to be effective on the costs. In addition, the proposed method in this study leads to determining the fleet size and capacity for transportation and the appropriate transportation mode.
Keywords: EXTERNAL COSTS; FREIGHT; RAIL; ROAD; OPERATIONS; INVENTORY; ALGORITHM; EMISSIONS; SELECTION; TRUCKING; Science & Technology - Other Topics